Molecular analysis of Taro and Bali cattle using cytochrome oxidase subunit I (COI) in Indonesia - Ni Nyoman Werdi Susari; I Putu Suastika; Kadek Karang Agustina (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Susari NNW, Suastika P, Agustina KK. 2021. Molecular analysis of Taro and Bali cattle using cytochrome oxidase subunit I (COI) in Indonesia. Biodiversitas 22: 165-172. Cytochrome oxidase subunit I (COI) is one of the molecular markers often used as a differentiator with many advantages in phylogeny analysis, and it thus rarely undergoes substitution. This research was conducted to characterize the genetics of Taro and Bali (Bos javanicus) cattle. Blood from the animals was collected from the jugularis vein and amplified by PCR. The target area was COI with a primer that was successfully amplified, namely the forward BICOIF (5'-TTC-TCAACCAACCATAAAGATATTGG-3') and the reverse BICOIR fragment (5'-TAG-ACTTCGGGGTGTCCAAAGAATCA-3'). The PCR products' sequencing was carried out by phylogeny analysis using MEGA 6 software. The amplicon value that succeeded in electrophoresis was 710bp, while six polymorphic sites were obtained at base positions of 1, 300, 379, 675, 676, and 679. The haplotypes (Hap) obtained were 4, with a genetic distance that ranged from 0.000-0.001. The nitrogenous bases of the amino acid composition from the samples showed no significant difference. The phylogenetic tree (Tamura-Nei) classified the cattle into two clades with a genetic distance of 0.0005.